Topography and microrelief electroless Ni-P coatings at different loading densities - Igor V. Petukhov; Natalia A. Medvedeva (Конденсированные среды и межфазные границы)
The aim of this study was to investigate the growth processes of Ni-P coatings at different loading densities of the electroless nickel plating bath. The Ni-P coatings can be used to improve the thermal and corrosion resistance of optical fiber used to manufacture sensors of various physical quantities.